Endogenous Opioid and Receptors in Panic Disorder - Dandachi, Abdulkader; Yudiarso, Ananta; Alzouabi, Kousay (Faculty of Psychology, Universitas Surabaya, 2007)
The aim of this article is to explore the role of endogenous opioid thou@ their recqto s p, 6, K, and o on respi- hen in panic disorder. An opioideqgc dysfunction as pathophysiological mechanism underlying panic disorda was proposed in some previous studies. In this mini review, we focused on (a) role of endogenous opioid as modulator for carbon dioxide dvity and (b) the effect of the opioid receptors on respiration in mtal studies using opioid antagonist Artikel ini bermaksud mengeksplomsi pemn endogenous opioid melalui qioid receptor p, 6, and o pada panapasan pada gangpan panik I>lsfimgsl opiodergic sebagai mekanisme patofisiologis telah dii dalam beberapa kajian sebelumnya. Dalam mini raiaY ini kami fokuskan bahasan pada kajian (a) pemn endogenous opioid sebagai modulator dvitas terhadap kahmdiosida dan (b) efek opioid receptor pada panapasan dalam kajian eksperimental yang menggunakan dmi&mi antagonist opioid